2013
DOI: 10.1103/physreve.88.052908
|View full text |Cite
|
Sign up to set email alerts
|

Generalized synchronization in relay systems with instantaneous coupling

Abstract: We demonstrate the existence of generalized synchronization in systems that act as mediators between two dynamical units that, in turn, show complete synchronization with each other. These are the so-called relay systems. Specifically, we analyze the Lyapunov spectrum of the full system to elucidate when complete and generalized synchronization appear. We show that once a critical coupling strength is achieved, complete synchronization emerges between the systems to be synchronized, and at the same point, gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…Heterogeneous units with both amplitude and phase dynamics profit from their amplitude dynamics [which is neglected in phase (Kuramoto) oscillators] to lower the synchronization threshold. Further, studies on synchronization in networks of oscillators indirectly coupled through a medium (the so-called relay and remote synchronization) highlighted the role of heterogeneity in inducing or enhancing synchronization [23][24][25][26][27][28][29]. Here, we also emphasize the enhancing effect of heterogeneity on synchronization.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Heterogeneous units with both amplitude and phase dynamics profit from their amplitude dynamics [which is neglected in phase (Kuramoto) oscillators] to lower the synchronization threshold. Further, studies on synchronization in networks of oscillators indirectly coupled through a medium (the so-called relay and remote synchronization) highlighted the role of heterogeneity in inducing or enhancing synchronization [23][24][25][26][27][28][29]. Here, we also emphasize the enhancing effect of heterogeneity on synchronization.…”
Section: Introductionmentioning
confidence: 71%
“…Many factors affect the synchrony of coupled oscillators, e.g., the coupling strength [17], the number of coupled oscillators [18], the network topology [19,20], or the heterogeneity [21][22][23][24][25][26][27][28][29]. In [21], the authors reported an enhancement of synchrony in an array of Josephson junctions with disorder, which refers to the situation in which the elements of the array are not identical.…”
Section: Introductionmentioning
confidence: 99%
“…Some demonstrations of chaotic masking of communication as well as selected secure communication lines were observed. Gutiérrez et al in [22] showed that a generalized synchronization (GS) in relay systems with instantaneous coupling could be obtained. The authors proved the existence of GS in unidirectional coupled units (drive system → response system) by checking the ability of the response system to react identically to different initial conditions of the same driver system, which can be quantified by evaluating the mutual false nearest neighbors or by measuring the conditional Lyapunov exponents.…”
Section: Complexitymentioning
confidence: 99%
“…The phenomenon is even more varied when more than two units interact according to a pattern of connectivity through which they share information about their current state: complete synchronization [6], phase synchronization [7], cluster synchronization [8], partial synchronization [9], chimera states [10,11], relay synchronization [12], and remote synchronization [13] are only examples of the behaviors observed in a network of coupled oscillators. For complete synchronization as investigated in this paper, a series of well-known results provides the conditions for the onset of the synchronous motion.…”
Section: Introductionmentioning
confidence: 99%